Specific features of pregnancy in patients with type 1 diabetes in the prepubertal period. Results of a 15-year long clinical observation - Lyubov' Leonidovna Bolotskaya; Natalya Vladimirovna Efremova; Yury Ivanovich Suntsov (Сахарный диабет)
Aim. To evaluate effect of different factors on pregnancy course in patients with type 1 diabetes mellitus developing in the prepubertal period. Materials and methods. The study based at Endocrinological Research Centre included 77 women with prepubertal diabetes 18 of whom developedpregnancy that ended in delivery. Results. As per 2009, the age of the patients is 26,6?4,6 years. They became pregnant at 23,2?3,3 years and had had diabetes since the age of9,6?4,8 years. Their HbA1c level before and after pregnancy was 8,6?1,4 and 6,8?1,6% respectively, the difference being insignificant (p=0,3).Significant difference was documented between these HbA1c levels and that during pregnancy (p=0,0004 and 0.003 respectively). Nine (56,2%) patientsused ultrashort-acting insulin analogs and the remaining 7 (43,7%) recombinant human insulins. The mean insulin dose was 43,7?11 U/din the 1st trimester, 51,8?13,7 U/d in the 2bd trimester, and 45,3?10,8 U/d after delivery. 16 (88%) of the patients reported frequent hypoglycemia,five (27,8%) of them had episodes of severe daytime and nocturnal hypoglycemia. 11 (61%) developed microvascular diabetic complications beforepregnancy, with 9 (50%) having DR and 4 (22,2%) DN (microalbuminuria). The delivery occurred on weeks 36-37 in 7 (38,9%) women. Naturaland cesarean section deliveries took place in one and 17 (94,4%) patients respectively. Conclusion. Long-term follow-up of patients wit DM1 in accordance with algorithms of specialized medical aid to DM1 patients in Russia at a multidisciplinaryendocrinological centre decreases the risk of pregnancy and delivery complications and that of microvascular diabetic complications